A phase 1 trial of autologous stem cell transplantation conditioned with melphalan 200 mg/m2 and total marrow irradiation (TMI) in patients with relapsed/refractory multiple myeloma. Issue 7 (3rd July 2018) - Patel, Pritesh; Oh, Annie L.; Koshy, Matthew; Sweiss, Karen; Saraf, Santosh L.; Quigley, John G.; Khan, Irum; Mahmud, Nadim; Hacker, Eileen; Ozer, Howard; Peace, David J.; Weichselbaum, Ralph R.; et al.
Abstract: In this phase 1 study, we tested increasing doses of total marrow irradiation (TMI) in addition to standard intravenous melphalan at 200 mg/m 2 (Mel200) in the conditioning regimen prior to autologous stem cell transplant (ASCT) for multiple myeloma (NCT02043847). Twelve patients aged 18–75 with relapsed myeloma were enrolled in the study and received Mel200 and TMI 3 Gy ( n = 3), 6 Gy ( n = 3), or 9 Gy ( n = 6) prior to transplant. There were no grade 4 extra-hematologic toxicities and a maximum tolerated dose was not reached. Median time to neutrophil and platelet engraftment was 11 and 13 d, respectively. At day 90, 73% of patients were in CR or VGPR. Median progression free survival (PFS) was 449 d and median overall survival (OS) was 966 d. We conclude that TMI at a dose of 9 Gy can be safely combined with Mel200 in therapeutic regimens for autologous transplant. Initial clinical results will prompt a phase 2 study.